Increasing power generation to a single-chamber compost soil urea fuel cell for carbon-neutral bioelectricity generation: A novel approach - Magotra, Verjesh Kumar; Lee, Dong-Jin; Kim, D. Y.; Lee, S. J.; Kang, T. W.; Magotra, Arjun; Inamdar, Akbar I.; Shrestha, Nabeen K.; Patil, Supriya A.; Thammanu, Siriluck; Jeon, Hee Chang (Frontiers in Microbiology, 2023)
Microbial fuel cells (CS-UFC) utilize waste resources containing biodegradable materials that play an essential role in green energy. MFC technology generates “carbon-neutral” bioelectricity and involves a multidisciplinary approach to microbiology. MFCs will play an important role in the harvesting of “green electricity.” In this study, a single-chamber urea fuel cell is fabricated that uses these different wastewaters as fuel to generate power. Soil has been used to generate electrical power in microbial fuel cells and exhibited several potential applications to optimize the device; the urea fuel concentration is varied from 0.1 to 0.5 g/ml in a single-chamber compost soil urea fuel cell (CS-UFC). The proposed CS-UFC has a high power density and is suitable for cleaning chemical waste, such as urea, as it generates power by consuming urea-rich waste as fuel. The CS-UFC generates 12 times higher power than conventional fuel cells and exhibits size-dependent behaviour. The power generation increases with a shift from the coin cell towards the bulk size. The power density of the CS-UFC is 55.26 mW/m2. This result confirmed that urea fuel significantly affects the power generation of single-chamber CS-UFC. This study aimed to reveal the effect of soil properties on the generated electric power from soil processes using waste, such as urea, urine, and industrial-rich wastewater as fuel. The proposed system is suitable for cleaning chemical waste; moreover, the proposed CS-UFC is a novel, sustainable, cheap, and eco-friendly design system for soil-based bulk-type design for large-scale urea fuel cell applications.